Incidence of central diabetes insipid us among the patients undergoing pituitary tumor surgery 06 through trans-sphenoidal approach (Journal of Surgical Sciences, 2019)
Background: Diabetes insipidus (DI) is a common complication following pituitary surgery. Thiscondition can be transient or permanent and the signs and symptoms of this disorder can bemimicked by the normal postoperative course.Objective: This study was carried out to find out the incidence of central diabetes insipidus (DI)among the patients undergoing pituitary tumor surgery through trans-sphenoidal approach eitherendoscopic or microsurgical for the first time.Study Design: Cross sectional observational studyMethods: Patients with central (Neurogenic) diabetes insipidus prior to surgery, co-morbiditieslike diabetes mellitus, kidney diseases, electrolyte imbalance, recurrent cases were excludedfrom this study. Patients were followed up to 7th postoperative day by recording and analyzingfindings of postoperative serum electrolytes, urinary specific gravity, hourly urinary volume forestablishing diabetes insipid us.Results: 76.9% of patients developed diabetes insipidus and 70.0% of patients did not developdiabetes insipid us those who underwent pituitary tumour surgery by trans-sphenoidal endoscopicapproach; 23.1% of patients developed diabetes insipid us and 30.0% of patients did not developdiabetes insipid us those who underwent pituitary tumour surgery by trans-sphenoidal mlcrosurgicalapproach.Conclusion: Prediction of DI help us in pre-operative counseling and post-operative managementof the patients as well as to reduce complications related morbidity after pituitary tumor surgery.Journal of Surgical Sciences (2017) Vol. 21 (1) :6-10